Vehicle product-line strategy under dual-credit and subsidy back-slope policies for conventional/new energy vehicles. (March 2023) - Liu, Li; Wang, Zhe; Liu, Yingyan; Zhang, Zaisheng
Highlights: Subsidy back-slope policy reduces the economic benefits of NEVs. Credit pricing mechanism can alleviate the negative impact of subsidy back-slope. Credit price and technology capability affect automakers' product-line strategies. Automakers' technology capabilities affect the effects of government intervention. Abstract: This study considers a monopoly automaker under dual-credit and subsidy back-slope policies to explore the automaker's optimal product-line strategies and the impacts of the two policies on the economy and environment. By constructing a stylized pricing model that takes heterogeneous consumption preferences into account, we investigate how two policy programs, i.e., considering both dual-credit policy and subsidy back-slope policy (DS program) and only dual-credit policy (D program), affect the automaker's product-line strategies, and determine the optimal vehicle pricing, energy-saving level and carbon emissions. The automaker has three product-lines strategies, i.e., conventional vehicle line (CV, C-plan), new energy vehicle line (NEV, N-plan), and CV-NEV line (M-plan). Then, sensitivity analyses are given to examine the impacts of exogenous variables (NEV credit price, subsidy back-slope) and endogenous variables (NEV technology capacity) on the automaker's strategies. The results show that the automaker's NEV technology capacity plays a vital role in the development of the environmentally friendly auto industry. Only when the technology capability reaches a certain threshold, the automaker is willing to take the initiative to produce NEVs. Subsidy back-slope can cause the sales countercurrent of NEVs, which can be alleviated by the NEV credit pricing mechanism.